Estimation of gaseous pollutants emitted from Al-Najybia Power station in Basra - Abdullah, Asia S. (University of Thi-Qar Journal of Science, 2019)
The objective of the present study was to estimate selected gaseous pollutants generated from Al- Najybia power station in Basra, south of Iraq. The highest concentration was found is carbon monoxide, estimated at 18.4 ppm followed by nitrogen dioxide 7.01E-03 ppm and 8.14E-04 ppm for hydrogen sulphide gases estimated in the area of 1 kilometre away from Al- Najybia power station. The concentrations of these toxic gases were decreased as we move away from Al- Najybia station. However, the concentrations in the station 4 which is 4 kilometre away were found to be high compared to the normal concentrations of these gases in the atmospheric air.